EFFECTS OF CALCIUM ANTAGONISTS OF THE THIRD GENERATION IN PATIENTS WITH ARTERIAL HYPERTENSION AND CONCOMITANT CHRONIC OBSTRUCTIVE PULMONARY DISEASE - D. A. Yakhontov; N. F. Balabanova (Столичная издательская компания, 2016)
Aim. To study antihypertensive efficacy and safety of amlodipine maleate as well as its influence on respiratory function, C reactive protein plasma level, glucose and lipid metabolism in patients with arterial hypertension (HT) and chronic obstructive pulmonary disease (COPD).Material and methods. 50 patients with HT 1-3 grade and COPD I-II stage in remission were randomized into two groups. 31 patients of the first group were treated with amlodipine maleate (Stamlo-M) 5-10 mg/d alone or in combination. 19 patients of the second group received any other antihypertensive therapy except dihydropyridine calcium antagonists.Results. Amlodipine in combined therapy has high antihypertensive efficacy providing achievement of target blood pressure levels and improvement of 24-hour blood pressure profile. Amlodipine therapy improved respiratory function and reduced systolic blood pressure in pulmonary artery. Amlodipine has no negative influence on metabolic status, did not increase sympathetic activity, and reduced C reactive protein levels. It demonstrated good tolerability and safety.Conclusion. High antihypertensive efficacy, improvement of respiratory function, and safety allows recommending amlodipine maleate (Stamlo-M) for usage in hypertensive patients with COPD.